Impacts of Global Warming on Energy Use for Heating and Cooling with Full Rebound Effects in Switzerland - Camille Gonseth; Philippe Thalmann; Marc Vielle (Swiss Journal of Economics and Statistics, 2017)
This paper analyzes the impacts of the modified needs for space heating and cooling due to global warming on the quantities of energy used for space conditioning and overall. It thereby estimates direct and total rebound effects, the latter including changes in consumption and production triggered by changes in energy needs for space conditioning by households, services and industry. A computable general equilibrium model is used to simulate a range of climate and impacts scenarios for Switzerland over the period 2010–2060. We find significant welfare gains from reduced heating needs, exceeding largely the costs of the additional electricity needed for cooling. We also find large rebound effects. For instance, while the climate scenario A1b would allow households to reduce their consumption of fossil energy for room heating by 15.9 %, actual reductions are only 10.4%, which implies a direct rebound effect of 35 %. Economy wide, fossil energy consumption could decrease by 4.3% but does so only by 2.7%, which represents a total rebound effect of 37%.
Keywords: C63; Q41; Q54; 330; climate change; heating; cooling; computable general equilibrium model; Switzerland; adaptation; rebound effect